Surgical proficiency grading and outcome of fistula repair; does it really matter? (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To measure and validate the outcome of fistula repair with FIGO surgical proficiency grading.Methods: Review of obstetric fistula managed at University College Hospital/Adeoyo fistula center was done. The lead expert fistula surgeon trainer at FIGO certified fistula training center graded all trainee surgeons and fistula complexity. Data was collected using a structured proforma. The fistula characteristics,level of surgeon and surgical outcomes were assessed. Analysis was done using SPSS version 25. Level of significance was set at P